Abscisic Acid Inhibition of Radicle Emergence But Not Seedling Growth Is Suppressed by Sugars - Finkelstein, Ruth R. (American Society of Plant Physiologists, 2000)
Low concentrations of sugars altered the sensitivity of seed germination to inhibition by exogenous abscisic acid (ABA). Germination of wild-type and ABA-insensitive (abi) Arabidopsis seeds was assayed on media containing ABA and a variety of sugars and sugar alcohols. The inhibitory effects of ABA were strongly repressed in the presence of 15 to 90 mm glucose (Glc), sucrose, or fructose, but not by comparable concentrations of sorbitol or mannitol. Several features of the response to Glc are inconsistent with a purely nutritional effect: The optimal sugar concentration is low and differs between the wild type and the abi mutants. Furthermore, Glc suppression of ABA inhibition is light dependent and limited to the process of radicle emergence.